Enamel matrix derivative and low-level laser therapy in the treatment of intra-bony defects: a randomized placebo-controlled clinical trial - Onur Ozcelik (Blackwell Synergy, 2008)
Aim: The aim of this study was to evaluate the immediate post-operative pain, wound healing and clinical results after the application of an enamel matrix protein derivative (EMD) alone or combined with a low-level laser therapy (LLLT) for the treatment of deep intra-bony defects. Material and Methods: This study was an intra-individual longitudinal test of 12 months’ duration conducted using a blinded, split-mouth, placebo-controlled and randomized design. In 22 periodontitis patients, one intra-bony defect was randomly treated with EMD1LLLT, while EMD alone was applied to the contra-lateral defect site. LLLT was used both intra- and post-operatively. Clinical measurements were performed by a blinded periodontist at the time of surgery, in the first week and in the first, second, sixth and 12th month. Visual analogue scale (VAS) scores were recorded for pain assesment. Results: The results have shown that the treatment of intra-bony defects with EMD alone or EMD1LLLT leads to probing depth reduction and attachment-level gain. In addition, EMD1LLLT had resulted in less gingival recession (po0.05), less swelling (po0.001) and less VAS scores (po0.02) compared with EMD alone. Conclusion: This study shows that EMD is an effective, safe and predictable biomaterial for periodontal regeneration and LLLT may improve the effects of EMD by reducing post-operative complications.